Peningkatan Kualitas Pembelajaran Dan Digitalisasi Sekolah Berbasis Learning Management System Di Madrasah Aliyah Al-Imam Sawoo - Muhammad Irkham Firdaus; Abdul Aziz; Fauzi Alfatoni; Friska Setiya Pamungkas; Angger Raafiu (Kreativasi : Journal of Community Empowerment, 2022)
Currently, educational institutions are required to have an innovation that can support educational and teaching activities, such as combining the education system with an informatics system. However, there are still many educational institutions that do not know much about informatics technology, such as Madrasah Aliyah Al-Imam Sawoo, so this community service activity aims to provide innovation and improve the quality of education by implementing an internet-based education system or learning management system. This is attempted so that the aims and objectives of education can be carried out as well as possible by adjusting to the times, especially since many students at Madrasah Aliyah Al-Imam Sawoo already have electronic devices in the form of cell phones and laptops. This PKM activity uses socialization, training, and mentoring methods. In this PKM activity, it provides a new innovation in helping education and teaching activities, namely a special digital platform for MA Al-Imam Sawoo. The platform uses Moodle, which is a special digital platform that can be accessed both via the Web and mobile. Thus, it can be a solution for teaching and learning that is effective and in accordance with the times. and become new solutions and innovations that MA Al-Imam Sawoo uses in their daily learning process in the hope that this method will improve the quality of learning and provide new colors to students in their teaching and learning activities at school.